Laparoscopic Donor Nephrectomy : A Step-by-Step Guide - Desai, Mahesh R.; Ganpule, Arvind P. (Springer Singapore : Imprint: Springer, 2017)
This book explains the development of various laparoscopic donor nephrectomy (LDN) techniques, which can be performed via the retroperitoneal or the transperitoneal approach. It provides a step-by-step explanation of LDN, including details of intricacies such as port positioning, dissection steps, securing the hilum and retrieval. It also reviews new techniques like robotic donor nephrectomy and single-port donor nephrectomy. Lastly, it explores the non-technical but equally important issues of donor work-up and legal and social aspects. LDN is a unique surgical procedure in which the surgeon operates on an individual who is not a patient but someone donating out of altruistic motives, and it has to be "zero error" for the safety of the graft, donor and the recipient. This handbook is a valuable resource for urologists, general and transplant surgeons as well as anesthesiologists and medical social workers working in the field.